Demand and Supply of Money in a Developing Economy: A Structural Analysis for India - Bhattacharya, B. B. (The Review of Economics and Statistics, 1974)
RECENT studies by Teigen (1964), Smith (1967) and Modigliani, Rasche and Cooper (1970) suggest that money supply like money demand is sensitive to the interest rate. This has two implications: (a) the supply of money may not be an exogenous variable; and (b) the ordinary least squares estimates of the money demand function with the interest rate as an explanatory variable may suffer from simultaneous-equation bias. In this case-study of India we shall investigate some of these familiar issues in monetary economics as well as some monetary issues peculiar to developing economies. In developed countries, in general, discrepancies between physical and monetary flows of production, consumption and income are only marginal.' In developing countries sizable proportions of income and consumption originate through non-monetary transactions like self consumption of goods and services and barter trade. These proportions generally decline with economic development.2 The transaction demand for money therefore increases partly because of growth of national income and partly because of a rise in the degree of monetization.3 As such, the relevant concept of income in monetary analysis of developing countries is a monetized component of national income and not total national income. This factor has been generally ignored in empirical studiesprobably because of the lack of data on monetized income. In this study we have estimated the money demand function with monetized income data and have shown how it differs from that estimated with national income data.4 Another important characteristic of developing economies is the dual nature of organized and unorganized money market interest rates. In the organized market the speculative demand for money varies with interest rates on financial assets. Interest rates in the unorganized market are primarily related to risks and returns on real assets which having inelastic supply like land.5 The supply of money does not effect these interest rates significantly. Therefore, the Keynesian liquidity preference hypothesis may hold good in developing economies, if at all, in the organized market rather than the unorganized market. In section II we formulate the money supply and the money demand functions for the Indian economy within the framework of a HicksHansen-Modigliani-type model. The ordinary least squares (OLS) and the two-stage least squares (2-SLS) estimates of these functions with alternative definitions of money are analysed in section III. The impact of nonmonetized income and unorganized market interest rate on money demand are analysed in section IV. Section V is devoted to the analysis of forecasts and multipliers of 'money proper (currency plus demand deposits). The main conclusions are presented in section VI.